"Paper or Plastic?": How We Pay Influences Post-Transaction Connection. Issue 5 (6th November 2015) - Shah, Avni M.; Eisenkraft, Noah; Bettman, James R.; Chartrand, Tanya L.
Abstract : Does the way that individuals pay for a good or service influence the amount of connection they feel after the purchase has occurred? Employing a multi-method approach across four studies, individuals who pay using a relatively more painful form of payment (e.g., cash or check) increase their post-transaction connection to the product they purchased and/or the organization their purchase supports in comparison to those who pay with less painful forms of payment (e.g., debit or credit card). Specifically, individuals who pay with more painful forms of payment increase their emotional attachment to a product, decrease their commitment to nonchosen alternatives, are more likely to publicly signal their commitment to an organization, and are more likely to make a repeat transaction. Moreover, the form of payment influences post-transaction connection even when the objective monetary cost remains constant and when the psychological cost is indirect (i.e., donating someone else's money). Increasing the psychological pain of payment appears to have beneficial consequences with respect to increasing downstream product and brand connection.